2000
DOI: 10.1002/1097-4636(20010305)54:3<320::aid-jbm20>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Porous bioactive glass and glass-ceramics made by reaction sintering under pressure

Abstract: A glass and a rhenanite-wollastonite glass-ceramic were synthesized with the qualitative composition Na2O-CaO-SiO2-P2O5. Both materials were prepared by reaction sintering under isostatic pressure (RSIP) using powder mixtures. Solid state reactions were complete within a few hours at 950 degrees C under modest pressure. Formation of the glass and crystalline phases was driven by an intermediate, reactive, low viscosity Na2O-SiO2 phase. A reaction mechanism is suggested. Porous materials were obtained with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The phase analysis revealed that the glass and the b-TCP reacted during the thermal treatment, giving rise to the formation of rhenanite (NaCaPO 4 ) and wollastonite (CaSiO 3 ), similarly to what has been reported in the literature for analogous HA/bioglass composites. 133,294 The reaction mechanism, originally proposed by Gong et al, 294 is described by the following equations:…”
Section: B-tcp/bioglass Composites: a Brief Overviewmentioning
confidence: 99%
“…The phase analysis revealed that the glass and the b-TCP reacted during the thermal treatment, giving rise to the formation of rhenanite (NaCaPO 4 ) and wollastonite (CaSiO 3 ), similarly to what has been reported in the literature for analogous HA/bioglass composites. 133,294 The reaction mechanism, originally proposed by Gong et al, 294 is described by the following equations:…”
Section: B-tcp/bioglass Composites: a Brief Overviewmentioning
confidence: 99%
“…Brittleness and slow degradation rates are disadvantages associated with their use. Gong et al fabricated glass implants with 5% porosity and pores that ranged from 100–200 µm to the <10 µm range, and also glass-ceramic implants with macropores (100–200 µm) and micropores (<5 µm) [110]. Glassy carbon pellets with 40% porosity induced bone in-growth in tibia defects in rabbits [111].…”
Section: Porous Biomaterials In Orthopaedic and Dental Applicationsmentioning
confidence: 99%
“…28 Glass ceramics containing NaCaPO 4 were also reported to be bioactive. 29,30 Therefore, the resulting glass ceramic powders from the starting nanoparticles possess high biocompatibility.…”
Section: Resultsmentioning
confidence: 99%